Pro-Angiogenic Effects of Canine Platelet-Rich Plasma: In Vitro and In Vivo Evidence - Seong-Won An; Young-Sam Kwon (Animals, 2025)
Platelet-rich plasma (PRP) is widely applied in veterinary regenerative medicine due to its rich composition of growth factors that promote tissue repair. However, the direct pro-angiogenic function of canine PRP (cPRP) has not been thoroughly validated through controlled in vitro and in vivo experimentation. Human umbilical vein endothelial cells (HUVECs) were used to assess cell proliferation, migration, and tube formation after exposure to cPRP. In addition, a rabbit corneal micropocket assay was employed to evaluate in vivo angiogenic responses. Treatment with 20% cPRP significantly enhanced HUVEC proliferation and migration and induced robust tube formation. In the in vivo model, we observed dose-dependent neovascularization, with the earliest vascular sprouting seen on day 1 in the 40% group. Both models consistently demonstrated that cPRP stimulates vascular development in a concentration-dependent manner. This study provides novel evidence of cPRP’s capacity to induce neovascularization, supporting its therapeutic value for treating nonhealing wounds in dogs, especially in cases involving chronic inflammation, aging, or immune dysregulation. These findings offer a scientific foundation for the broader clinical application of cPRP in veterinary regenerative practice.